A biocultural examination of trauma from the Colorado State Insane Asylum skeletal collection, 1879-1899 - Leavitt-Reynolds, Alissa Anne, author; Magennis, Ann L., advisor; Van Buren, Mary, committee member; Fiege, Mark T., committee member (Colorado State University. Libraries, 2011)
This thesis uses a biocultural approach to study skeletal trauma present in the Colorado State Insane Asylum (CSIA) Skeletal Collection from 1879 to 1899. The biocultural approach utilizes both the physical remains and historic documentary material present for this collection to connect the skeletal findings with the cultural environment in which the individuals lived and died. Of the 166 individuals present (both complete and incomplete), 69% in the collection show at least one instance of trauma, while 31% show no evidence of trauma. This trauma rate includes both fractures and dislocations, or acute trauma, in addition to chronic trauma (Schmorl's Nodes). Males have the highest traumatic injury rates, with 40% of the sample having one or more fractures or dislocations. Females show a rate of 29% for acute trauma, while indeterminate sex individuals have a rate of 38%. The trauma results were then compared with contemporary, mostly Euroamerican, skeletal collections from the Albany Almshouse and the Oneida Asylum in New York to reveal that while all three institutions show similar rates of chronic trauma, the CSIA Collection has much higher rates of acute trauma -- nearly double that of the other populations. Ultimately, the analysis of trauma as undertaken in this research provides yet another line of evidence to better understand and contextualize the health and health risks of individuals and populations from the nineteenth-century American West, and more specifically, those in institutionalized care during that time.
Keywords: asylum; bioarchaeology; institutionalization; osteology; skeleton; trauma